Pengaruh Inovasi Produk, Promosi, dan Diskon Terhadap Frekuensi Pembelian pada Smartphone POCO di Bekasi - Atmaja, Robbi; Kurniawan, Ravi; Saepul Anwar , M Riyan; Purnamasari, Pupung (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study examines the effects of product innovation, promotion, and discounts on the purchase frequency of Poco smartphones in Bekasi. Employing a quantitative approach with 65 respondents selected through purposive sampling, the results indicate that product innovation significantly influences purchase frequency, outweighing promotion and discounts. Effective promotional strategies and attractive discounts also play crucial roles. SmartPLS analysis reveals robust research instruments with high Cronbach’s Alpha values. The findings explain 77.5% of the variance in purchase frequency. This study emphasizes integrating product innovation with omnichannel marketing strategies to enhance customer engagement and loyalty, providing strategic insights for Poco to improve competitiveness and customer retention.